Pivotal role of Helicobacter pylori virulence genes in pathogenicity and vaccine development - Elbehiry, Ayman; Marzouk, Eman; Abalkhail, Adil; Sindi, Wael; Alzahrani, Yasir; Alhifani, Salem; Alshehri, Turki; Anajirih, Nuha Abdulaziz; ALMutairi, Turki; Alsaedi, Ahmad; Alzaben, Feras; Alqrni, Abdullah; et al. (Frontiers in Medicine, 2025)
One of the most prevalent human infections is Helicobacter pylori (H. pylori), which affects more than half of the global population. Although H. pylori infections are widespread, only a minority of individuals develop severe gastroduodenal disorders. The global resistance of H. pylori to antibiotics has reached concerning levels, significantly impacting the effectiveness of treatment. Consequently, the development of vaccines targeting virulence factors may present a viable alternative for the treatment and prevention of H. pylori infections. This review aims to provide a comprehensive overview of the current understanding of H. pylori infection, with a particular focus on its virulence factors, pathophysiology, and vaccination strategies. This review discusses various virulence factors associated with H. pylori, such as cytotoxin-associated gene A (cagA), vacuolating cytotoxin gene (vacA), outer membrane proteins (OMPs), neutrophil-activated protein (NAP), urease (ure), and catalase. The development of vaccines based on these virulence characteristics is essential for controlling infection and ensuring long-lasting protection. Various vaccination strategies and formulations have been tested in animal models; however, their effectiveness and reproducibility in humans remain uncertain. Different types of vaccines, including vector-based vaccines, inactivated whole cells, genetically modified protein-based subunits, and multiepitope nucleic acid (DNA) vaccines, have been explored. While some vaccines have demonstrated promising results in murine models, only a limited number have been successfully tested in humans. This article provides a thorough evaluation of recent research on H. pylori virulence genes and vaccination methods, offering valuable insights for future strategies to address this global health challenge.